The real and desirable gender schema between high school students and working people - Stojanowska, Elżbieta (Studia Psychologica: Theoria et praxis, 2007)
The present study was performed to describe real and desirable gender schema in men and women group: university students and working people in middle adulthood. IPP - Polish version Bem Sex Role Inventory – was used to measure gender schema. Results indicated that there were bigger differences among men and women with reference to the real than the desirable gender schema. Women were more feminine than men and men were more masculine than women, however most subjects desired to have higher level male than female traits, with the exception of women working in female stereotyped professions who wanted to have the same level of both kinds’ traits. The age of subjects differentiated gender schema only in women groups: younger women, compared with working women, were more androgynous and more often desired to have androgynous schema.